Electromagnetically induced transparency and bound in continuum states in double Aharonov-Bohm coupled rings. (2019) - Mrabti, T.; Labdouti, Z.; El Boudouti, E.H.; Fethi, F.; El Abouti, O.; Djafari-Rouhani, B.
Abstract: We investigated electromagnetic induced transparency (EIT) resonances and bound in continuum (BIC) states in a simple mesoscopic structure made of double Aharonov-Bohm rings of lengths d 1 and d 2 threaded by a magnetic flux and coupled by a wire of length d 0 . These investigations are accomplished through an analysis of the amplitude of the transmission coefficient obtained using the Green's function method. This structure may exhibit a large band gap and an EIT resonance in the transmission spectrum without introducing any impurity in one arm of the loop. In addition, we show that the shape of the EIT resonances and the width of the band gaps can be tuned by means of the magnetic flux and the geometry of the structure. These results may have important applications for electronic transport in mesoscopic systems.